Organ donation and family refusal. Bioethical reasons for a change - Zúñiga-Fajuri, Alejandra; Molina-Cayuqueo, José (Revista de Nefrología, Diálisis y Trasplante, 2018)
Cases of next-of-kin veto, i.e., a family refusal to allow organs harvest contrary to donor wishes or when the law presumes consent, is a widespread practice that seriously harms thousands of people. This is a practice settled in many countries Family refusal to donate reduces an already shallow donor pool by approximately 43% in the Americas, 25% in Europe (37,3% in United Kingdom) and 54% in Asia. Some countries, such Argentina, France, Colombia and Wales, current reversed its policy on organ donations to a system that prevents next of kin to dishonoring the donor’s wishes restricting the confirm donor status only with the National Donor Registry and unless evidence of their objection is produced. In part I we review the latest amended transplant legislation of those countries that are trying to change this scenario. In part II we question the most frequently cited arguments to uphold the next-of-kin veto right and the countries that successfully changed their legislation banning this practice to encourage organ donation. We conclude that it is imperative to change this practice because the harm caused by promoting the family veto is greater and more serious than the potential harm of not allowing it.